Gas adsorbent, battery pole piece, battery diaphragm and battery
By using COF or MOF materials and the gas adsorbent of the cladding layer in sodium ion batteries, the gas influence generated by side reactions in the battery is solved, the battery capacity protection and the electrolyte stability are achieved, and the battery capacity reduction is avoided and Ineffective.
Patent Information
- Application Number
- CN202411116036.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-17
AI Technical Summary
In sodium ion batteries, the electrode material reacts with the electrolyte at a high voltage state, resulting in the generation of carbon dioxide gas, causing internal swelling of the battery, affecting the circulation performance, and the gas adsorption materials of the prior art cannot effectively isolate the electrolyte, resulting in battery capacity decline.
Use gas adsorbents including COF or MOF materials and cladding layers. The cladding layer is graphene oxide, single-layer graphene and other materials, which are used to isolate electrolytes. COF or MOF materials have high adsorption capacity and small particle size, and exist. Acid or alkaline functional groups can effectively adsorb carbon dioxide and prevent the electrolyte reaction through the cladding layer.
Effectively prevent battery inflation, maintain electrolyte wetting, reduce electrolyte consumption, reduce capacity loss of positive and negative electrodes, and prevent battery failure.
Smart Images

Figure CN119153829A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a gas adsorbent, a battery pole piece, a battery separator and a battery. Background Art
[0002] The electrode materials in sodium ion batteries react chemically with the components in the electrolyte under high voltage conditions, resulting in a side reaction of decomposition of the electrolyte and impurities and the production of the main gas carbon dioxide, which causes swelling inside the battery and affects the battery's cycle performance. Some prior arts use porous materials such as hard carbon and soft carbon as the negative electrode of the battery. The porous material is used to adsorb the gas, but the adsorbed gas will occupy the effective adsorption sites of sodium and reduce the wettability of the electrolyte and the capacity of the negative electrode. In order to improve the gas produced by the side reactions in the battery, a gas adsorption unit made of a metal organic framework material is still provided, such as the invention patent with publication number CN118263552A. However, the inventors found that the metal organic framework material will also react with the electrolyte, consuming the electrolyte and the metal organic framework material. There are also aluminum-plastic films that eliminate flatulence, such as the invention patent with publication number CN 106450046 B. The water-resistant and anti-flatulence aluminum-plastic film for lithium battery packaging disclosed in the invention has a scratch-resistant layer, an aluminum foil layer, a chemical protective layer, an absorption layer and a barrier layer from the outside to the inside. There are adhesive layers between the scratch-resistant layer and the aluminum foil layer, between the chemical protective layer and the absorption layer, and between the absorption layer and the barrier layer. The aluminum foil layer and the chemical protective layer are formed together. However, this method cannot discharge the gas adsorbed between the battery electrode layers in time, so that the gas is still adsorbed on the surface of the battery electrode, affecting the interface between the battery electrode and the electrolyte, resulting in a loss of battery capacity. Summary of the invention
[0003] The main purpose of the present invention is to provide a gas adsorbent, a battery pole piece, a battery separator and a battery to solve the technical problems in the prior art that the battery pole piece produces gas, resulting in a decrease in battery capacity, and that the electrolyte and the metal organic framework material react.
[0004] In order to achieve the above objectives, the first aspect of the present invention provides a gas adsorbent, comprising a COF material or a MOF material and a coating layer coated on the surface of the COF material or the MOF material, wherein the coating layer is used to isolate the electrolyte.
[0005] Furthermore, there are acidic functional groups or basic functional groups on the COF material or MOF material.
[0006] Furthermore, the coating layer is one or more of graphene oxide, single-layer graphene, carbon layer, sodium salt of organic hydroxyl compound, sodium difluorophosphate, polyethylene oxide, sodium propionate-1,2-13C2, sodium carbonate, sodium oxide and sodium fluoride.
[0007] Furthermore, the adsorption capacity of the COF material or MOF material is higher than 0.2 mmol / g, and the particle size is less than 60 μm.
[0008] Furthermore, the MOF material is one or more of Cu-MOF-74, Zn-MOF-5, and Cu-HKUST-1.
[0009] A second aspect of the present invention provides a battery pole piece, comprising a current collector and a battery separator, wherein the battery separator is located on at least one surface of the current collector, and the battery separator is formed by coating a slurry on the current collector, and the slurry includes the gas adsorbent described in the above embodiment.
[0010] Furthermore, the slurry further comprises an active substance, a binder, a conductive agent and a solvent, and the mass percentage of the gas adsorbent to the total of the active substance, the binder and the conductive agent is 0.05% to 5%.
[0011] Furthermore, the amount of the gas adsorbent added is based on the formula: M = N / n, where M is the mass of the MOF material or COF material, N is the molar mass of the gas generated by the reaction between the battery electrode and the electrolyte, and n is the molar mass of the gas adsorbed per gram of MOF material or COF material.
[0012] A third aspect of the present invention provides a battery separator, comprising the gas adsorbent described in the above embodiment, wherein the gas adsorbent is coated on the battery separator.
[0013] A fourth aspect of the present invention provides a battery, comprising the above-mentioned battery pole piece and / or the above-mentioned battery separator.
[0014] Beneficial effects:
[0015] A gas adsorbent of the present invention comprises a COF material or a MOF material and a coating layer coated on the surface of the COF material or the MOF material, wherein the coating layer is used to isolate the electrolyte. The COF material or the MOF material can adsorb and fix carbon dioxide, prevent flatulence and affect the liquid-solid interface between the positive and negative electrodes and the electrolyte, and can reduce the consumption of the electrolyte to a certain extent, ensure that the battery pole piece has good wettability, and avoid the loss of battery capacity; the coating layer does not dissolve in the electrolyte, maintains a certain gas transmission channel, isolates electrons and retains ion channels, and prevents the electrolyte from reacting with the COF material or the MOF material. The gas generated by the battery is fixed by the gas adsorbent, and the addition of the gas adsorbent to the battery pole layer can more effectively compete with the adsorption of the positive and negative active substances, which can reduce the capacity loss of the positive and negative electrodes due to the adsorption of gas, and will not allow its volume to expand and cause battery failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1This is a scanning electron microscope image of a battery electrode in one embodiment of the present invention.
[0017] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0018] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0019] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0020] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0021] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0022] One embodiment of the present invention provides a gas adsorbent, including a COF material or a MOF material and a coating layer coated on the surface of the COF material or the MOF material, wherein the coating layer is used to isolate the electrolyte. The COF material or the MOF material can adsorb and fix carbon dioxide, prevent flatulence and affect the liquid-solid interface between the positive and negative electrodes and the electrolyte, and can reduce the consumption of the electrolyte to a certain extent, ensuring that the battery pole piece has good wettability; the coating layer does not dissolve in the electrolyte, maintains a certain gas transmission channel, isolates the electron retention ion channel, and prevents the electrolyte from reacting with the COF material or the MOF material.
[0023] In the above embodiments, both the MOF material (metal organic framework material) and the COF material (conjugated organic framework material) have highly ordered pore structures, which provide a large amount of surface area for adsorbing carbon dioxide generated by decomposition of the electrolyte. Carbon dioxide molecules interact with the surface of the MOF material or COF material through van der Waals forces and are adsorbed inside the pores to achieve physical adsorption.
[0024] In one embodiment, there are acidic functional groups or basic functional groups on the COF material or MOF material. The acidic functional groups and basic functional groups in the COF material or MOF material can react chemically with carbon dioxide to form chemical bonds. For example, acidic groups include hydroxyl groups, phenolic groups, alcohol groups, carboxyl groups, sulfonic acid groups, etc.; basic groups include amine groups, amino groups, SH, etc. The adsorption performance of MOF materials can be adjusted by synthesizing different organic ligands and metal ion combinations to adjust the acidity and alkalinity to enhance the adsorption capacity of carbon dioxide.
[0025] In one embodiment, the coating layer is one or more of graphene oxide, single-layer graphene, carbon layer, sodium salt of organic hydroxyl compound (NaOR), sodium difluorophosphate (NaPO2F2), polyethylene oxide (PEO), sodium propionate-1,2-13C2 (CH3CH2CO2Na), sodium carbonate (Na2CO3), sodium oxide (Na2O) and sodium fluoride (NaF). The COF material or MOF material is coated with these coating materials, and the treatment method can be vapor deposition, solution impregnation, electrochemical deposition, etc. Preferably, a small amount of nano-scale coating material can be fully wrapped on the surface of the COF material or MOF material by vapor deposition. The materials of these coating layers are the main components of SEI film and CEI film in sodium ion batteries, and can well block the reaction between electrolyte and COF core or MOF core. The COF core is the organic element connected by covalent bonds constituting the COF skeleton, and the MOF core is the metal ion or metal cluster constituting the MOF skeleton.
[0026] In one embodiment, the adsorption capacity of the COF material or MOF material is higher than 0.2 mmol / g, and the particle size is less than 60 μm. The adsorption capacity is a property of the COF material or MOF material, which is related to its own pore size, functional groups and other factors; since the thickness of the battery pole piece is generally 100 to 300 μm, it is necessary to control the particle size of the coating applied on the current collector.
[0027] In one embodiment, the MOF material is one or more of Cu-MOF-74, Zn-MOF-5, and Cu-HKUST-1. These MOF materials are organic frameworks composed of copper ions or zinc ions and organic ligands, wherein the organic ligands of Cu-MOF-74 are usually phthalic acid, the organic ligands of Cu-HKUST-1 are usually trimesic acid, and Zn-MOF-5 is a hexagonal MOF material composed of 1,4-phthalic acid and zinc ions. In Zn-MOF-5, the carboxyl group of 1,4-phthalic acid forms a coordination bond with the zinc ion, and the benzene ring forms a pore structure through the π-π stacking interaction caused by the overlap of the π electron cloud. This pore structure makes Zn-MOF-5 have a large specific surface area and pore volume, which is conducive to the adsorption and storage of gas molecules.
[0028] Another embodiment of the present invention provides a battery pole piece, including a current collector and a battery separator, wherein the battery separator is located on at least one surface of the current collector, and the battery separator is formed by coating a slurry on the current collector, wherein the slurry includes any of the gas adsorbents described above. The battery pole piece is made by coating a slurry uniformly mixed with the gas adsorbent on the current collector and then die-cutting, and the gas adsorbent realizes the function of adsorbing carbon dioxide at the battery pole piece level, and there is no gas on the surface of the battery pole piece, which will not affect the liquid-solid interface between the battery pole piece and the electrolyte, so that the battery pole piece is fully immersed in the electrolyte.
[0029] In the above embodiment, the slurry also includes active material, binder, conductive agent and solvent, and the mass percentage of the gas adsorbent to the total of the active material, binder and conductive agent is 0.05% to 5%. If the positive electrode sheet is prepared, the positive electrode active material is added to the mixture of binder, conductive agent and solvent, and the positive electrode active material is usually layered metal oxide, polyanion compound, Prussian blue, etc., and the gas adsorbent is added; on the contrary, when preparing the negative electrode sheet, the added negative electrode active material is hard carbon, soft carbon, metal oxide, etc. Among them, the mass percentage of the active material is 90%-98%; the binder is one of PVDF and PAN, and the mass percentage is 1%-5%; the conductive agent includes one of sp / VGCF / CNTs / ECP, and the mass percentage is 1%-5%.
[0030] In the above embodiment, the mass percentage of the gas adsorbent to the total mass of the active material, the binder and the conductive agent is 0.05% to 5%. Specifically, the amount of the gas adsorbent added is based on the formula: M=N / n, wherein M is the mass of the MOF material or the COF material, N is the molar mass of the gas generated by the reaction between the battery electrode and the electrolyte, and n is the molar mass of the gas adsorbed per gram of the MOF material or the COF material, that is, the adsorption capacity.
[0031] Preferably, in the positive electrode sheet, the gas adsorbent accounts for 0.05% to 2% of the total of the positive electrode active material, the binder, and the conductive agent; in the negative electrode sheet, the gas adsorbent accounts for 0.1% to 2% of the total of the negative electrode active material, the binder, and the conductive agent; the compaction density of the positive and negative electrodes is not the same, and the proportion of the gas adsorbent may also be different. The proportion of the gas adsorbent is determined based on the gas production and the adsorption capacity of the gas adsorbent.
[0032] Another embodiment of the present invention provides a battery separator, comprising the gas adsorbent described in any one of the above embodiments, wherein the gas adsorbent is coated on the battery separator. The gas adsorbent mixed with a binder is sprayed on the battery film, and after drying, a battery separator containing a gas adsorbent coating is obtained, so that the positive electrode sheet and the negative electrode sheet can directly contact the battery separator to achieve the same effect.
[0033] Another embodiment of the present invention provides a battery, comprising the battery pole piece and / or battery separator in the above embodiment. Before liquid injection, the battery is first vacuum-baked at 60-100°C for 12-24 hours to decompose the MOF material or COF material, remove part of the adsorbed carbon dioxide to ensure the adsorption capacity, and use nitrogen for gas washing. It is vacuum-stored before liquid injection and sealed after liquid injection to ensure the carbon dioxide capture and adsorption capacity of the MOF material or COF material.
[0034] In the above embodiment, the assembled battery is prone to thermal runaway when subjected to high temperature conditions above 90 to 300°C. The MOF material or COF material in the gas adsorbent will collapse and precipitate carbon dioxide. The carbon dioxide is separated between the positive and negative electrodes, reducing the contact rate of the positive and negative electrodes, reducing the flash point of the combustible gas to a certain extent, inhibiting open flame combustion, and slowing down thermal runaway.
[0035] In order to more clearly illustrate the present invention, the following examples are given, but they do not limit the scope of the present invention in any way.
[0036] Example 1
[0037] The gas adsorbent is coated on the current collector through the positive electrode slurry. The COF / MOF material in the gas adsorbent is NH2-CU-MOF-74, and its adsorption capacity is 4mmol / g. The gas adsorbent accounts for 1% of the total of the positive electrode active material, binder and conductive agent. The positive electrode sheet is formed by die cutting, and the surface density of the positive electrode sheet is 3g / 100cm 2 The sodium ion battery cell with a composition volume of 400 ml has a total mass of 3 g of gas adsorbent and can adsorb 240 mL of carbon dioxide. The cell was subjected to cycle and storage tests, and the volume changes before and after the cycles and storage were compared.
[0038] Example 2
[0039] The gas adsorbent is coated on the current collector through the negative electrode slurry. The COF / MOF material in the gas adsorbent is NH2-CU-MOF-74, and its adsorption capacity is 4mmol / g. The gas adsorbent accounts for 0.05% of the total of the positive electrode active material, binder and conductive agent. The negative electrode sheet is formed by die cutting, and the surface density of the negative electrode sheet is 2g / 100cm 2 The sodium ion battery cell with a volume of 400 ml has a total mass of 0.1 g of gas adsorbent and can adsorb 8 mL of carbon dioxide. The cell was cycled and stored to compare the volume changes before and after cycling and storage.
[0040] Example 3
[0041] The gas adsorbent is coated on the current collector through the negative electrode slurry. The COF / MOF material in the gas adsorbent is SH-Zn-MOF-5, and its adsorption capacity is 2.5mmol / g. The gas adsorbent accounts for 2% of the total of the negative electrode active material, binder and conductive agent. The negative electrode sheet is formed by die cutting, and the surface density of the negative electrode sheet is 1.7g / 100cm 2 The sodium ion battery cell with a volume of 400 ml has a total mass of 8.5 g of gas adsorbent and can adsorb 477 mL of carbon dioxide. The cell was cycled and stored to compare the volume changes before and after cycling and storage.
[0042] Example 4
[0043] One side of the current collector is a mixture of negative electrode active material, binder, and conductive agent, and the other side of the current collector is a mixture of gas adsorbent and binder. Among them, the COF / MOF material is NO2-Zn-MOF-5, and its adsorption capacity is 2.5mmol / g. The gas adsorbent accounts for 5% of the total of negative electrode active material, binder, and conductive agent. After die-cutting, the negative electrode sheet is formed, and the surface density of the negative electrode sheet is 1.7g / 100cm 2The stacked cells form a sodium-ion battery cell with a volume of 400 ml. The total mass of the gas adsorbent is 5 g, and the amount of carbon dioxide adsorbed is 280 mL. The cells are cycled and stored to compare the volume changes before and after cycling and storage.
[0044] Example 5
[0045] The MOF material used in the gas adsorbent is NH-Co-MOF-74, and the particle size is less than 3μm. It is mixed with a binder and a solvent to form a mixed glue solution with a gas adsorbent accounting for 95%; the mixed glue solution is sprayed onto the surface of the PP film with a thickness of 30μm, and dried to form a battery separator containing a gas adsorbent coating. The stacked sheets form a sodium ion battery cell with a volume of 400ml, in which the total mass of the gas adsorbent on the battery separator is 2g, and the amount of carbon dioxide that can be adsorbed is 100mL. The battery cell is cycled and stored to compare the volume changes before and after cycling and storage.
[0046] Example 6
[0047] The gas adsorbent is coated on the current collector through the positive electrode slurry. The COF / MOF material in the gas adsorbent is CALF-20 (a three-dimensional porous structure assembled by zinc ions, 1,2,4-triazole and oxalate) coated with NaPO2F2, and its adsorption capacity is 5mmol / g. The gas adsorbent accounts for 0.05% of the total of the positive electrode active material, binder and conductive agent; the positive electrode sheet is formed by die cutting, and the surface density of the positive electrode sheet is 3g / 100cm 2 The sodium ion battery cell with a composition volume of 400 ml has a total mass of 0.15 g of gas adsorbent and can adsorb 168 mL of carbon dioxide. The cell was subjected to cycle and storage tests, and the volume changes before and after the cycles and storage were compared.
[0048] Example 7
[0049] The positive and negative electrode slurries containing gas adsorbents are coated on the current collectors, and the mixed glue consisting of binder, solvent and gas adsorbent is sprayed on the battery separator substrate; the COF / MOF material in the gas adsorbent is the coated NH2-Zn-MOF-5, and its adsorption capacity is 2.5mmol / g. When it is used in the positive electrode slurry, the particle size is less than 20μm, and the gas adsorbent accounts for 0.5% of the total of the positive electrode main powder, binder and conductive agent; when it is used in the negative electrode slurry, the particle size is less than 20μm, and the gas adsorbent accounts for 0.5% of the total of the negative electrode main powder, binder and conductive agent; when it is used in the positive electrode slurry, the particle size is less than 3μm; the gas adsorbent accounts for 1% of the total weight of the battery separator. After die-cutting, the positive and negative electrode sheets are formed, and the surface density of the positive electrode sheet is 3g / 100cm 2 The negative electrode surface density is 1.7g / 100cm 2The sodium ion battery cell with a composition volume of 400 ml has a total mass of 2.5 g of gas adsorbent and can adsorb 140 mL of carbon dioxide. The cell is cycled and stored to compare the volume changes before and after cycling and storage.
[0050] Comparative Example
[0051] Without adding any gas adsorbent, ordinary positive electrode sheets, negative electrode sheets and battery separators are used to assemble battery cells, and the battery cells are subjected to cycle and storage tests to compare the volume changes before and after cycling and storage.
[0052] The cycle and storage test results are shown in the following table:
[0053]
[0054]
[0055] The experiment found that adding gas additives directly to the positive or negative electrode sheet has the best effect. The capacity retention rate is 10% higher than that of the unadded gas additive after 500 cycles, and the volume is reduced by about 200ml. Figure 1 It can be seen that the gas additives are evenly distributed on the surface of the current collector and cover the main powders such as the active material. This is enough to show that the addition of gas additives can adsorb and fix the gas generated by the battery during the cycle process, greatly reducing the degree of flatulence, and allowing good contact between the electrolyte and the positive and negative electrodes. In addition, adding gas adsorbents to the battery electrode layer can more effectively compete with the adsorption of positive and negative active materials, which can reduce the capacity loss of the positive and negative electrodes due to the adsorbed gas, and will not allow their volume to expand and cause battery failure.
[0056] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A gas adsorbent, It is characterized in that It comprises a COF material or a MOF material and a coating layer coated on the surface of the COF material or the MOF material, wherein the coating layer is used for isolating the electrolyte.
2. The gas adsorbent according to claim 1, It is characterized in that The COF material or the MOF material has an acidic functional group or a basic functional group.
3. The gas adsorbent according to claim 1, It is characterized in that The coating layer is one or more of graphene oxide, single-layer graphene, carbon layer, sodium salt of organic hydroxyl compound, sodium difluorophosphate, polyethylene oxide, sodium propionate-1,2-13C2, sodium carbonate, sodium oxide and sodium fluoride.
4. The gas adsorbent according to claim 1, It is characterized in that The COF material or MOF material has an adsorption capacity higher than 0.2 mmol / g and a particle size smaller than 60 μm.
5. The gas adsorbent according to claim 1, It is characterized in that The MOF material is one or more of Cu-MOF-74, Zn-MOF-5, and Cu-HKUST-1.
6. A battery electrode, It is characterized in that The invention comprises a current collector and a battery separator, wherein the battery separator is located on at least one surface of the current collector, and the battery separator is formed by coating a slurry on the current collector, wherein the slurry comprises the gas adsorbent according to any one of claims 1 to 5.
7. The battery electrode according to claim 6, It is characterized in that The slurry also includes active material, binder, conductive agent and solvent, and the mass percentage of the gas adsorbent to the total of the active material, binder and conductive agent is 0.05% to 5%.
8. The battery pole piece according to claim 7, It is characterized in that The amount of the gas adsorbent added is based on the formula: M=N / n, where M is the mass of the MOF material or COF material, N is the molar mass of the gas generated by the reaction between the battery electrode and the electrolyte, and n is the molar mass of the gas adsorbed per gram of MOF material or COF material.
9. A battery separator, It is characterized in that The gas adsorbent according to any one of claims 1 to 5 is coated on the battery separator.
10. A battery, It is characterized in that It comprises the battery pole piece as described in any one of claims 6 to 8 and / or the battery separator as described in claim 9.
